Value-added taxes in Central and Eastern European countries - Cnossen, Sijbren...[et al.] (OECD ParisFR, 1998)
Examines the policy issues and administrative questions that arise in designing VAT systems for transition economies. Focuses on the ten countries from Central and Eastern Europe that have applied for membership of the European Union.